Prophenoloxidase activation is required for survival to microbial infections in Drosophila. - Binggeli, O.; Neyen, C.; Poidevin, M.; Lemaitre, B. (PLoS Pathogens, 2014)
The melanization reaction is a major immune response in Arthropods and involves the rapid synthesis of melanin at the site of infection and injury. A key enzyme in the melanization process is phenoloxidase (PO), which catalyzes the oxidation of phenols to quinones, which subsequently polymerize into melanin. The Drosophila genome encodes three POs, which are primarily produced as zymogens or prophenoloxidases (PPO). Two of them, PPO1 and PPO2, are produced by crystal cells. Here we have generated flies carrying deletions in PPO1 and PPO2. By analyzing these mutations alone and in combination, we clarify the functions of both PPOs in humoral melanization. Our study shows that PPO1 and PPO2 are responsible for all the PO activity in the hemolymph. While PPO1 is involved in the rapid early delivery of PO activity, PPO2 is accumulated in the crystals of crystal cells and provides a storage form that can be deployed in a later phase. Our study also reveals an important role for PPO1 and PPO2 in the survival to infection with Gram-positive bacteria and fungi, underlining the importance of melanization in insect host defense.